Tectonic Structure of Northern Sumatra Region Based on Seismic Tomography of P and S Wave Velocity - Silitonga, Betrix Elisabet; Suardi, Iman; Firmansyah, Akmal; Hanif, Muhammad; Ramdhan, Mohamad; Sembiring, Andry Syaly (Badan Riset dan Inovasi Nasional, 2023)
The tectonic setting of Sumatra Island is strongly influenced by the oblique subduction of the Indo-Australian Plate, which subducts the Eurasian Plate at a speed of 52–60 mm/year. The movement of these plates resulted in the Northern Sumatra region having seismic sources from tectonic and volcanic activity. The data used in this study is in the form of seismic wave travel-time recorded by numerous seismic stations in the research area from January 2012 to December 2020. The data comes from 5,003 earthquakes recorded by the BMKG seismic network. The inversion is a simultaneous inversion between seismic velocity models (Vp and Vs) and hypocenter parameters by applying a double-difference seismic tomography algorithm. Tomogram results in parts of Aceh (Singkil and Subulussalam) and North Sumatra (Pakpak Bharat and Dairi) at a depth of 0 km show negative perturbations in Vp and Vs values and high Vp/Vs values. The anomaly is most likely related to cracks in fluid-saturated rocks. The tomograms in the south of Lake Toba at depths of 30 km and 40 km have high Vp and Vs perturbation values and low Vp/Vs values. This anomaly indicates a magma supply line that is no longer active or has cooled for a long time. Based on the seismic tomography modeling results, the subducted Indo-Australian Plate to the Eurasian Plate is visible in the study area.